Interjective construccions and discourse operators of argumentative intensification - Fuentes Rodríguez, Catalina (Boletín de Filología, 2023)
The interjection is considered in some grammars as a class of words, other times it is included among the exclamatory groups. Its macrosyntactic behavior has been scarcely approached despite constituting a broad and dynamic paradigm. The interjection can act as an autonomous modal utterance or be included within the utterance performing various functions. The scope of the affected element in each case differs.This paper analyzes those contexts in which interjective terms with malsonant content develop procedural meanings of argumentative intensification. We describe their syntagmatic distribution, their scope and the constructions they generate. We also delimit whether we are dealing with free or semi-fixed constructions and in which cases we can already speak of grammaticalized discourse operators or those close to fixation.